From waste disposal to valuable material: Sulfonating polystyrene waste for heavy metal removal. Issue 5 (October 2020) - Tran, Anh T.K.; Pham, Thi Thuy; Nguyen, Quoc Hung; Hoang, Nhung T.T.; Bui, Duy Tan; Nguyen, Minh Ti; Nguyen, Manh Khai; Van der Bruggen, Bart
Highlights: Sulfonating polystyrene waste to form sulfonated functional groups for heavy metals removal. The adsorption of heavy metal by the sulfonated polystyrene fitted with both the Langmuir and the Freundlich isotherm model. he kinetic models of Thomas and Yoon-Nelson best described the simultaneous fixed-bed adsorption from a multi-metal system. Abstract: The conversion of waste into reusable materials has been a focus of many researchers in recent years. Polystyrene waste converted into a cation exchange resin and used as absorbent of cadmium, copper and zinc had been concerned. In this study, the feasibility of sulfonating polystyrene waste was investigated by using sulfuric acid to form sulfonated functional groups on the polystyrene matrix and further used for heavy metal ions removal from wastewater. The modified ion exchange materials were characterized by FTIR, SEM, EDS, XRD and TGA. Batch mode experiments of heavy metal ion exchange were conducted to determine the kinetic parameters. The adsorption of zinc, copper and cadmium by the sulfonated polystyrene fitted with both the Langmuir and the Freundlich isotherm model; the maximum adsorption capacities were 4.09 mg Zn 2+ /g, 4.58 mg Cu 2+ /g and 4.04 mg Cd 2+ /g, respectively. Moreover, fixed-bed adsorption was investigated. When the ﬂow rate decreased, the initial concentration, and the mass of sulfonated polystyrene increased, the adsorption capacity was observed to increase. A maximum adsorption capacity of 10.6 mg Zn 2+ /g was achieved at the inﬂuent concentration of 70 mg/L, sulfonated polystyrene mass of 30 g, and ﬂow rate of 8.33 mL/min when operating with real zinc electroplating wastewater. The kinetic Thomas and Yoon-Nelson models well described the adsorption of Zn 2+, Cu 2+, and Cd 2+ in continuous mode, with R 2 value higher than 90 %. From these results, it can be concluded that this sulfonation process of polystyrene waste can be technically and environmentally feasible method for sustainable development.